2020
DOI: 10.1111/os.12655
|View full text |Cite
|
Sign up to set email alerts
|

Crowe Type IV Hip Dysplasia Treated by THA Comebined with Osteotomy to Balance Functional Leg Length Discrepancy: A Prospective Observational Study

Abstract: Objective: To measure the factors that affect functional leg length of Crowe type IV Developmental dysplasia of the hip (DDH) patients and to review our own methods to balance leg length discrepancy (LLD) in Crowe type IV DDH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…As described in most literature, LLD is defined as the difference of the distance between a femoral and a pelvic landmark on both sides. 3 , 17 As a pelvic reference, the teardrop is used in many studies. 13 , 17 Because the teardrop is less affected by the position of the pelvis, it is more reliable than other pelvic landmarks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in most literature, LLD is defined as the difference of the distance between a femoral and a pelvic landmark on both sides. 3 , 17 As a pelvic reference, the teardrop is used in many studies. 13 , 17 Because the teardrop is less affected by the position of the pelvis, it is more reliable than other pelvic landmarks.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 17 As a pelvic reference, the teardrop is used in many studies. 13 , 17 Because the teardrop is less affected by the position of the pelvis, it is more reliable than other pelvic landmarks. In our study, we found the difference of the TD-TP and the difference of FL+TL had good correlation and reliability on patients’ perception.…”
Section: Discussionmentioning
confidence: 99%
“…As described in most literature LLD is de ned as the difference of the distance between a femoral and a pelvic landmark on both sides [4,17]. As a pelvic reference, the teardrop is used in many study [13,17]. Because the teardrop is less affected by the position of the pelvis, it is more reliable than other pelvic landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative fractures are likely to occur in 5.2%-26.8% of THA in cases of DDH [37][38][39][40]. Otherwise, if the femoral canal is too narrow to allow the insertion of the smallest stem, splitting of the femur, as proposed by Li et al [27], is an alternative.…”
Section: Complicationsmentioning
confidence: 99%
“…Several techniques, including transverse, oblique, z-shaped, or the double chevron osteotomy, have been proposed [23,24]. Current evidence suggests that THA combined with sub-trochanteric osteotomy is likely to provide satisfactory functional results [22,37,38,39]. If clinically significant limping is mentioned post-operatively, physical therapy and a shoe lift should be considered, as well as re-operation.…”
Section: Complicationsmentioning
confidence: 99%